Three‐Terminal Artificial Synapses: Recent Progress in Three‐Terminal Artificial Synapses: From Device to System (Small 32/2019). Issue 32 (9th August 2019) - Han, Hong; Yu, Haiyang; Wei, Huanhuan; Gong, Jiangdong; Xu, Wentao
Abstract : An electronic device that emulates synaptic plasticity is essential for building up a neuromorphic system. In article number1900695, Wentao Xu and co‐workers review recent progress in the design and fabrication of three‐terminal artificial synapses, and their applications in bioinspired systems such as tactile‐perception and light‐sensing actuation.